2009
DOI: 10.1002/ajhb.20994
|View full text |Cite
|
Sign up to set email alerts
|

Maternal capital and the metabolic ghetto: An evolutionary perspective on the transgenerational basis of health inequalities

Abstract: There is particular interest in understanding socioeconomic and ethnic variability in health status. The developmental origins of disease hypothesis emphasize the importance of growth patterns across the life-course in relation to noncommunicable disease risk. The physiological components of cardiovascular risk, collectively termed the metabolic syndrome, derive in part from a disparity between the homeostatic "metabolic capacity" of vital organs and the "metabolic load" induced by large tissue masses, a rich … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
274
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 232 publications
(281 citation statements)
references
References 210 publications
(226 reference statements)
5
274
0
2
Order By: Relevance
“…The present study found that the second-generation male offspring born to pre-pregnancy food deprived "grandmothers" were significantly heavier than those in other groups. We agree to previous hypotheses that pre-pregnancy undernutrition might exhaust mother's metabolic potential and impair adequate nutritional environment for the offspring (Wells 2003(Wells , 2010. Apparently, mother's body size adjusts to an energy saving regiment as an adaptation for an expected scarce resources environment (Gluckman et al 2005;McArdle et al 2006).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The present study found that the second-generation male offspring born to pre-pregnancy food deprived "grandmothers" were significantly heavier than those in other groups. We agree to previous hypotheses that pre-pregnancy undernutrition might exhaust mother's metabolic potential and impair adequate nutritional environment for the offspring (Wells 2003(Wells , 2010. Apparently, mother's body size adjusts to an energy saving regiment as an adaptation for an expected scarce resources environment (Gluckman et al 2005;McArdle et al 2006).…”
Section: Discussionsupporting
confidence: 77%
“…Thus, there is a particular need in research in the context of long-term outcomes such as aging, longevity and especially its inheritance to future generations. Furthermore, most studies concentrate on undernutrition solely during pregnancy, failing to examine the role of the period of formation of maternal metabolic capital, the pre-pregnancy period, that can be of crucial importance for the development of the fetus (Benyshek 2007;Wells 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism described above may involve either genetic adaptation, or mechanisms of plasticity, and at this stage neither can be ruled out 25 . Recently, it was proposed a new theoretical model for cardiovascular disease risk highlighting birth weight as an index of 'metabolic capacity' (organ structure and function that emerge during fetal life and infancy promoting the maintenance of homeostasis), and several factors in childhood (large tissue masses, sedentary behavior and high-fat diet) as indices of 'metabolic load' that challenge the ability to maintain homeostasis 26 . According to this model, body size and adiposity are predicted to increase metabolic load, whereas low birth weight is predicted to reduce metabolic capacity 26 .…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was proposed a new theoretical model for cardiovascular disease risk highlighting birth weight as an index of 'metabolic capacity' (organ structure and function that emerge during fetal life and infancy promoting the maintenance of homeostasis), and several factors in childhood (large tissue masses, sedentary behavior and high-fat diet) as indices of 'metabolic load' that challenge the ability to maintain homeostasis 26 . According to this model, body size and adiposity are predicted to increase metabolic load, whereas low birth weight is predicted to reduce metabolic capacity 26 . Metabolic load may be further exacerbated by sedentary behavior, which is associated with impaired motor performance during childhood with repercussions for young men.…”
Section: Resultsmentioning
confidence: 99%
“…Such growth penalties may take generations to resolve. Maternal short stature is a risk factor for obstructed labor, Caesarean section and low birth weight [171][172][173], potentially generating a long-term intergenerational cycle [15]. Contrasting with sperm production in men, women's ova are formed primarily early in life, and damage to the reproductive system in young girls, from infections, trauma or harmful substances, for example, can have long-term effects on their reproductive capacity and their children [174,175].…”
Section: Intergenerational Associationsmentioning
confidence: 99%